1998
DOI: 10.1183/09031936.98.11020392
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia reduces endothelin production by rat alveolar type II cells in primary culture

Abstract: Type II alveolar epithelial cells (ATII cells) have been shown to play a key role in the regulation of the alveolar space. ATII cells synthesize and secrete surfactant, control the volume and composition of the epithelial lining fluid and proliferate and differentiate into type I alveolar epithelial cells after injury in order to maintain the integrity of the alveolar wall. Moreover, ATII cells are ideally located to have a role in modulating the activation or proliferation state of macrophages, fibroblasts or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(53 reference statements)
2
4
0
Order By: Relevance
“…However, ET-1 secretion was suppressed by hypoxia and anoxia in pulmonary epithelial cells. This phenomenon has been reported previously for both A549 cells and primary rat alveolar type II cells [45]. Although animal studies indicate that ET-1 can exert profound effects on the function of alveolar epithelial cells, the mechanisms of ET-1 processing within alveolar epithelial cells are not known at this time.…”
Section: Discussionsupporting
confidence: 78%
“…However, ET-1 secretion was suppressed by hypoxia and anoxia in pulmonary epithelial cells. This phenomenon has been reported previously for both A549 cells and primary rat alveolar type II cells [45]. Although animal studies indicate that ET-1 can exert profound effects on the function of alveolar epithelial cells, the mechanisms of ET-1 processing within alveolar epithelial cells are not known at this time.…”
Section: Discussionsupporting
confidence: 78%
“…In agreement with this possibility, there are some reports on the expression of ET in this cell type (Rozengurt et al, 1990;Giaid et al 1993;Crestani et al 1998). The secretion of surfactant by Type II pneumocytes has been reported to be stimulated by ET (Sen et al 1994).…”
Section: Discussionsupporting
confidence: 62%
“…However, an increased arterial ET-1 level in hypoxemic COPD patients seems to be in contrast with some recent experimental findings. Crestani et al [14]recently showed that hypoxemia reduces ET production of rat alveolar type II cells in primary culture. Jankov et al [15]demonstrated that in neonatal rats, hyperoxia caused increased ET-1 levels and PH.…”
Section: Discussionmentioning
confidence: 99%